2017
DOI: 10.20450/mjcce.2017.1070
|View full text |Cite
|
Sign up to set email alerts
|

Analytical study of the XIV century wall painting and lime mortars in the "St. George" church in Staro Nagoričane, Republic of Macedonia

Abstract: This work presents the first comprehensive study of the wall painting in the "St. George" church accomplished mainly by means of Fourier Transform Infrared Spectroscopy using Diffuse Reflectance and Micro-Infrared method (FTIR/DRS/Micro-IR) and the other analytical techniques Optical microscopy (OM), X-Ray Fluorescence (XRF), X-Ray Diffraction (XRD) and Inductively Coupled Plasma -Mass Spectrometry (ICP-MS). The main research objective was characterization of the artistic palette and painting technique, but al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…), were able to dissolve CaCO 3 , which found to be the base material of the Lan Na’s mural painting in this study. The dissolution of this calcium compound may result from secondary metabolite secreting from the microorganism which could cause severe damage to the paint layers ( Čukovska et al, 2017 ). We further found that isolate SK1, Trichaptum sp., was able to form calcium crystals which could further crack the paint layer and deteriorate the painting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), were able to dissolve CaCO 3 , which found to be the base material of the Lan Na’s mural painting in this study. The dissolution of this calcium compound may result from secondary metabolite secreting from the microorganism which could cause severe damage to the paint layers ( Čukovska et al, 2017 ). We further found that isolate SK1, Trichaptum sp., was able to form calcium crystals which could further crack the paint layer and deteriorate the painting.…”
Section: Discussionmentioning
confidence: 99%
“…Biomineralization is the process by which living organisms influence the precipitation of mineral materials ( Skinner and Ehrlich, 2014 ). The formation of salt or calcium compound can also lead to the deconstruction of the painting’s layer, as it could increase the pressure on the mural materials and crack the artwork ( Pérez-Alonso et al, 2004 ; Piñar and Sterflinger, 2009 ; Čukovska et al, 2017 ; Suphaphimol et al, 2022 ). Due to the ability of microorganisms to cause mural deterioration, as described above, it is of utmost importance to observe and investigate the possible threats that these organisms pose to a mural painting.…”
Section: Introductionmentioning
confidence: 99%